Gross and Histological Studies on the Soft Palate Tonsil in Domestic Pig (Sus scrofa domesticus). - Damini V; Prasanth Babu A; Santhi Lakshmi M; Bharathi S; Sharon Nancy Nikhila K.P; Raja K; Supriya B; Kalyan Chakravarthy M (Indian Journal of Veterinary Anatomy, 2026)
The present study describes the gross and microanatomical features of the soft palate tonsil in domestic pigs. Grossly, the tonsils appeared as elongated oval plaques with numerous fossules on the mucosal surface of the soft palate. Histologically, the tonsil was lined by non-keratinzed stratified squamous epithelium with numerous crypts extended deeply into the lymphoid tissue of the tonsil. Each crypt consisted of a neck formed by epithelial invagination and a body by lymphoepithelium.